Wastewater systems and energy saving in urban India: governing the Water-Energy-Food Nexus series - Babette Never (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
This paper analyses the interdependency of water and energy in India's wastewater sector. Wastewater treatment plants consume a great deal of energy. Energy-efficient technologies are available, but are only spreading slowly in developing countries. In India, only 10% of all wastewater generated is treated, while energy demand is soaring. The case for investments in energy-efficient solutions thus seems clear. This case study analyses under which conditions and with which instruments integrated approaches to the water, energy and food (land) sectors (WEF-Nexus) are useful in various different wastewater systems across the country. It focuses on the identification of existing drivers of and barriers to the diffusion of energy-efficient technologies in India's urban wastewater sector, uncovering how investments in resource- and lifecycle-oriented solutions could be enhanced. Key findings are that India's urban wastewater sector is still largely in a situation of lock-in although first innovative initiatives that focus on more resource-footprint, lifecycle-oriented approaches exist in some niches. The diffusion of energy-efficient technologies is driven by pricing, mandatory regulations and standard-setting that are gradually being tightened. The privatization of building, operation and maintenance of treatment plants together with green procurement can be helpful if designed carefully. The main barriers against technology diffusion and a shift of the sector towards integrated approaches are a lack of cost recovery; vested interests in the status quo; a lack of operation and maintenance skills; and complicated processes, with many agencies and bureaucratic layers involved. Land and water scarcity are found to be catalytic to a change in planning, depending on local conditions.
Keywords: 330; Energie; Wasser